PDK4 gene positively regulates fat deposition in ovine adipocytes - Xiao, Cheng; Yang, Shaoying; Zhao, Wenjun; Liu, Yu; Fang, WenWen; Miao, Lisheng; Li, Xin; Cao, Yang; Jin, Haiguo; Cao, Yang (Frontiers in Nutrition, 2025)
IntroductionIntramuscular fat (IMF) content is a crucial factor affecting meat quality and flavor in sheep. Our previous studies demonstrated that the pyruvate dehydrogenase kinase 4 (PDK4) expression increases during adipocyte differentiation and is positively correlated with IMF content in sheep. However, the effects of the PDK4 gene on lipid metabolism in ovine adipocytes remain unclear.MethodsThe effects of PDK4 overexpression on ovine adipocyte differentiation and fat deposition were investigated. Subsequently, the key lipids and genes affected by PDK4 overexpression were identified using lipidomic and transcriptomic sequencing. Furthermore, a PDK4-knockout NIH/3T3 cell line was generated to verify the evolutionarily conserved functions of PDK4 and to examine the expression of candidate genes in a murine model.ResultsPDK4 overexpression significantly increased triglyceride deposition by 2.32-fold in ovine adipocytes (p = 0.001) but did not affect PPARγ mRNA or protein expression levels (p > 0.05). A total of 80 differentially expressed lipids (DELs) and 24 differentially expressed genes (DEGs) were identified between the overexpression (Over) and negative control (NC) groups, including 20 upregulated DELs, 60 downregulated DELs, 21 upregulated DEGs, and 3 downregulated DEGs. Additionally, PDK4 overexpression altered lipid content, composition, carbon chain length, and degree of unsaturation in ovine adipocytes. TMEM273, one of the DEGs, was negatively affected by PDK4 overexpression and closely correlated with 7 DELs (adjusted p < 0.01, |R| > 0.9). In the murine cell model, PDK4 knockout of NIH/3T3 (KO) cells significantly decreased triglyceride deposition by 0.77-fold (p < 0.01) but did not affect BSCL2 expression (p = 0.08). TMEM273 expression was significantly increased by 2.78-fold in pre-differentiated KO cells (p = 0.018) and significantly decreased by 0.83-fold in differentiated KO cells (p = 0.005).ConclusionPDK4 positively regulates fat deposition in both ovine and murine adipocytes. TMEM273 expression is negatively affected by PDK4 and correlated with lipid metabolism in sheep and mice.